Hurley, The 1960S - Greenwald, Richard (Teaching History: A Journal of Methods, 2001)
The 1960s is a book designed primarily for the junior high school grades. The format of the book, as with the series (Opposing Viewpoints Digests), is to take an important topic and present the pros and cons on specific subtopics. Jennifer Hurley’s hot topics include the Vietnam war, civil rights and feminism, and the larger cultural impact of the I 960s on contemporary American culture.